Sudden Unexpected Postnatal Collapse Resulting in Newborn Death in the United States. Issue 3 (May 2021) - Anderson, Tatiana M.; Ferres, Juan M. Lavista; Ramirez, Jan-Marino; Mitchell, Edwin A.
Abstract: Background: The sudden collapse of an apparently healthy newborn, or sudden unexpected postnatal collapse (SUPC) is fatal in about half of cases. Epidemiological characteristics of sudden unexpected infant death (SUID) in the first week of life differ from those in the postperinatal age group (7-365 days). Aim: To describe the characteristics of SUPC resulting in neonatal death. Methods: We analyzed the Centers for Disease Control and Prevention Birth Cohort Linked Birth/Infant Death Data Set (2003-2013: 41, 125, 233 births and 37, 624 SUIDs). SUPC was defined as infants born ≥35 weeks gestational age, with a 5-minute Apgar score of ≥7, who died suddenly and unexpectedly in the first week of life. Results: Of the 37, 624 deaths categorized as SUID during the study period, 616 met the SUPC criteria (1.5/100, 000 live births). Eleven percent occurred on the first day of life and nearly three quarters occurred during postnatal days 3-6. SUPC deaths differed statistically from SUID deaths occurring 7-364 days of age, in particular for sex, marital status, and live birth order. Implications: These data support the need for adequate nurse staffing during the immediate recovery period and for the entire postpartum stay as well as nurse rounding for new mothers in the hospital setting. Abstract : The sudden collapse of an apparently healthy newborn, known as sudden unexpected postnatal collapse (SUPC), is fatal in about half of cases. Death of a healthy newborn in the hospital setting is tragic; some cases are likely preventable. In this study, analysis of SUPC cases from 2003 to 2013 involving review of over 41 million US births found a rate of SUPC of 1.5/100, 000 live births with an estimated 22% occurring in the hospital setting. Newborn hospital safety recommendations from the Association Women's Health, Obstetric, and Neonatal Nurses and other professional organizations are included.